Metode Pembayaran Cash On Delivery (Cod) Melalui Jasa Ekspedisi PT. Pos Indonesia Jember Dalam Analisis Fatwa Dsn Mui Nomor 113/Dsn-Mui/Ix/2017 Tentang Akad Wakalah Bi Al-Ujrah - Ahmad, Zakiyyah Ilma; Roziq, Ahmad; Abidin, Ahmad Zainul (Jurnal Ilmiah Ekonomi Islam, 2024)
Cash on delivery (COD) is a payment method where buyers can pay for orders in cash when the order arrives at its destination delivered by a courier. PT. Pos Indonesia Jember will ask for wages for the work handed over to it with payment of a fee. The term regarding representation with payment of wages in Islam is called the wakalah bi al-ujrah contract which is contained in the DSN MUI fatwa number 113/DSN-MUI/IX/2017 concerning wakalah bi al -ujrah. The type and approach of this research is an empirical juridical approach or what is called field research. The data collection techniques used were structured interviews, participant observation and document study. Data analysis used in this research used descriptive-qualitative. This research concluded that wakalah contracts and ijarah contracts have been regulated separately in the Compilation of Sharia Economic Law but do not regulate wakalah bi al-ujrah contracts. This wakalah bi al-ujrah contract has only been regulated in the DSN MUI Fatwa number 113/DSN-MUI/IX/2017. Therefore, this wakalah bi al-ujrah contract is required for valid transactions according to sharia principles, so it can be added that in Perma Number 2 of 2008, especially in the wakalah contract, Chapter -ujrah, namely a wakalah contract accompanied by a fee so that it can accommodate cash on delivery payment method transactions through PT expedition services. POS Indonesia Jember Regency and can be operated by PT. POS Indonesia Jember Regency. So the wakalah bi al ujrah will have power if it enters into KHES as positive law or ius constitutum, namely the law that is currently in force or the law that has been established (positive law).